Pengaruh Profesionalisme, Penerapan Kode Etik, Dan Time Budget Pressure Terhadap Kualitas Audit (Studi Empiris pada Auditor di KAP Surakarta dan Yogyakarta) - Adi, Febrian Syam; , Dra. Nursiam, M.H., Ak., CA (2016)
The objectives of this research to empirically analyze the influence of professionalism, applying of etik code, and time budget pressure to audit quality, especially in the auditor working in KAP Surakarta and Yogyakarta. The population in this research are all auditors who worked on the KAP in Surakarta and Yogyakarta. Sampling was conducted using a convenience sampling method and number of samples of 35 respondents. Primary data collection method used is questionnaire method. The data are analyzed by using technical analyze Multiple Regression Analyze. The results showed that the effect on the profesionalism and applying of etik code of audit quality have influence on audit quality. While the interaction of time budget pressure don't have influence on audit quality. The coefficient of determination shows that jointly profesionalism, applying of etik code, and time budget pressure contributed to the dependent variable (quality audit) is 89,9% while the remaining 10,1% is influenced by other factors outside of observation.